Competitor’s analysis: an empirical study on SIRIM QAS International Sdn. Bhd. / Nurhamizah Amenzah - Amenzah, Nurhamizah (Faculty of Business and Management, 2010)
The main issue of this report is on analysis towards competitors of SIRIM QAS International Sdn. Bhd. I manage to know some of the competitors from the Corporate Affairs and Marketing Department. They keep track the competitors from time to time in order to compete aggressively. The purpose of this study is to know which part of competitor’s must be analyzed. The important point may help SIRIM QAS International Sdn. Bhd. to know the strength and weaknesses of themselves and also competitors. The method that I am using to get information is by observing the competitor’s website. Normally, they state all of information directly. Since I have been assign by the department to analyze the competitor’s website, I get more experience and get to know the competitors better. Then, I am also referring to other types of secondary data such as journal, pamphlet and websites to complete this report. The expected finding from this study can be use by the Affairs and Marketing Department to know the other way of analyzing competitors other than the SWOT itself. They may use it as reference to success and get higher achievement compare to the others.